Reasonable Notice Criteria in Common Law Wrongful Dismissal Cases - McShane, Steven L. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
An empirical study to analyse the criteria that Canadian courts have used to determine the length of notice to award.